AKULTURASI GOSPEL DALAM MUSIK GEREJA KHARISMATIK DI INDONESIA - Bayu Wijayanto (Institut Seni Indonesia Surakarta, 2010)
This article cope to elaborate an perception to aspect of influence Gospel as cultural element of Afro-Amerika, specially influence Gospel to culture of music of Christian Charismatic church in Indonesia. Aspect of Influence Gospel which require to be studied are elements of what entering as influence, where that elements enter, and also any kind of later on happened to the cultural elements of Gospel in Indonesia, specially in community of Christian Charismatic church. Cultural of music discussed in this case is music of Christian Charismatic church at a period of last two decade expanding at the time of Gospel start to look its influence. Approach Etnomusikologi done/conducted with the descriptive model analysis qualitative and comparability. Hereinafter subject of related to music aspect analysed and attributed to assorted of phenomenon, background, function, form the (structure) and its correlation with the structure ritual (divine liturgy). Analyse with the comparison and interpretation[of playing important role in this case. Especially to see the elements of according to, adaptation, variation and modify from element and music structure. Visible hereinafter there is change and continuity from element of music Gospel having an effect on to the church music elements. Key words : acculturation, music, gospel, charismatic church